Differences in the precision of performing the technical element - overhead passing skill of different age volleyball players - Nejic, K.; Curic, N.; Nejic, D.; Ljubic, Z.; Zafirovska Misovski, A. (Book of Proceedings Fis Communications 2019, 2019)
The aim of this study was to investigate the differences in the precision of performing the technical element of overhead passing skill of volleyball players of different ages. The study involved 60 male respondents, divided into two age groups. The first group consisted of respondents aged 15 to 17 years, and the second group consisted of respondents aged 17 and a half to 19 years. The measurements are carried out at the club "VGSK" in Veliko Gradiste. The study used a group of tests that were designed to determine the motor ability (precision) of a volleyball player in conducting of a given technical element. Based on the data it can be concluded that the differences between the older and the younger group of respondents regarding the passing the ball into the wall circle (t-value = -4.838, df. = 58, Sig. <.01) are statistically significant. In other words, there is a difference in the accuracy of overhead passing between the older and younger groups, with the older group (Mean = 13.73, Std. = 2.83, Std. Err = .52) performing better on this test than the younger group (Mean = 9.34, Std. = 4.08, Std. Err = .74). On the other hand, the results indicate that there is no statistically significant difference (t-value = -1.532, df. = 58, Sig. > .05) between the older and the younger group of respondents when it comes to the Elevational precision of overhead passing skill from the base position. Also, there is no statistically significant difference with respect to age (t . value = -1.478, df. = 58, Sig. > .05) when looking at the results of a test that measures the Elevational precision of jumping overhead passing skill.